FarmaREL: An Italian pharmacovigilance project to monitor and evaluate adverse drug reactions in haematologic patients. Issue 1 (3rd August 2017) - Fracchiolla, Nicola S.; Artuso, Silvia; Cortelezzi, Agostino; Pelizzari, Anna M.; Tozzi, Paola; Bonfichi, Maurizio; Bocchio, Federica; Gargantini, Livio; De Rosa, Elisa; Vighi, Giuseppe D.; Prestini, Lucia; Sammassimo, Simona; et al.
Abstract: Adverse drug reactions (ADRs) reduce patients' quality of life, increase mortality and morbidity, and have a negative economic impact on healthcare systems. Nevertheless, the importance of ADR reporting is often underestimated. The project "FarmaREL" has been developed to monitor and evaluate ADRs in haematological patients and to increase pharmacovigilance culture among haematology specialists. In 13 haematology units, based in Lombardy, Italy, a dedicated specialist with the task of encouraging ADRs reporting and sensitizing healthcare professionals to pharmacovigilance has been assigned. The ADRs occurring in haematological patients were collected electronically and then analysed with multiple logistic regression. Between January 2009 and December 2011, 887 reports were collected. The number of ADRs was higher in older adults (528; 59%), in male (490; 55%), and in non‐Hodgkin lymphoma patients (343; 39%). Most reactions were severe (45% required or prolonged hospitalization), but in most cases, they were fully resolved at the time of reporting. According to Schumock and Thornton criteria, a percentage of ADRs as high as 7% was found to be preventable versus 2% according to reporter opinion. Patients' haematological diagnosis, not age or gender, resulted to be the variable that most influenced ADR, in particular severity and outcome. The employment of personnel specifically dedicated to pharmacovigilance is a successful strategy to improve the number and quality of ADR reports. "FarmaREL", the first programme of active pharmacovigilance in oncohaematologic patients, significantly contributed to reach the WHO "Gold Standard" for pharmacovigilance in Lombardy, Italy.